2009
DOI: 10.1001/archoto.2009.164
|View full text |Cite
|
Sign up to set email alerts
|

A 25-Year Analysis of Veterans Treated for Tonsillar Squamous Cell Carcinoma

Abstract: In veterans treated for tonsillar SCC, we advocate the consideration of a treatment plan that includes surgery for patients presenting with advanced-stage SCC of the tonsil, even in patients with notable comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…The 5‐year local, regional, and locoregional controls rates were also excellent at 89%, 98%, and 88%, respectively. Table is a summary of studies published in the literature evaluating tonsillar SCC managed by primary surgery, radiation, or both . Some series have reported superior results, but these were primarily on patients with T1 and T2 primaries in which transoral tonsillectomies were carried out .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5‐year local, regional, and locoregional controls rates were also excellent at 89%, 98%, and 88%, respectively. Table is a summary of studies published in the literature evaluating tonsillar SCC managed by primary surgery, radiation, or both . Some series have reported superior results, but these were primarily on patients with T1 and T2 primaries in which transoral tonsillectomies were carried out .…”
Section: Discussionmentioning
confidence: 99%
“…Before the development of organ‐preservation protocols involving concurrent chemoradiation therapy, surgery followed by radiation therapy (RT) was the mainstay of treatment for patients with tonsillar SCC, with 5‐year disease‐specific survival (DSS) rates ranging from 61% to 75% . Over the past 15 years, improvements in chemoradiation have resulted in excellent locoregional control rates and DSS rates that are comparable to outcome results reported for traditional surgery .…”
Section: Introductionmentioning
confidence: 99%
“…Based on this plot, an argument could be made for further study of planned neck dissections in all N+ tonsil patients even in the absence of a residual palpable mass. A 25‐year retrospective review of tonsillar malignancy treatment regimens in a VA setting demonstrated that even after 1997, when 3D conformation radiation therapy became available at this institution and chemotherapy became more prevalently used, patients with advanced tonsillar malignancy who had surgical intervention had an improved disease specific survival and a nonsignificant trend toward improved overall survival, even in those with poor performance status 13. Report of significant improvement in overall survival when tonsillar cancers were treated with surgical resection followed by radiation therapy versus only radiation therapy was also reported by Poulsen;14 however, these patients were not regularly treated with concomitant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of their close proximity tongue base-SCCs, tonsil SCCs and soft palate SCCs have different clinical presentation and treatment outcomes [7]. In particular, tonsil SCCs have significantly better outcome (DSS and DFS) than tongue base SCCs [8]. …”
Section: Reviewmentioning
confidence: 99%